2007
DOI: 10.1007/bf03030657
|View full text |Cite
|
Sign up to set email alerts
|

Aging and senescence of the leaf organ

Abstract: Leaf senescence is a sequence of biochemical and physiological events comprising the final stage in leaf development. It encompasses the period from a fully expanded mature state up to the death, thereby limiting longevity. The changes occurring during leaf senescence are very complex but highly regulated, and are genetically programmed with actions coordinated at the cellular, tissue, organ, and organism levels. A major breakthrough in our molecular understanding of this phenomenon has been achieved through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 84 publications
0
32
0
2
Order By: Relevance
“…Numerous studies since have shown the cytokinins to be key regulators of senescence. For reviews of the role of cytokinin in development and senescence see Gan and Amasino (1996), Jameson (2003), Lim and Hong (2007) and Werner and Schmülling (2009). However, the key cytokinin regulatory genes have not been monitored during sequential leaf senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies since have shown the cytokinins to be key regulators of senescence. For reviews of the role of cytokinin in development and senescence see Gan and Amasino (1996), Jameson (2003), Lim and Hong (2007) and Werner and Schmülling (2009). However, the key cytokinin regulatory genes have not been monitored during sequential leaf senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf senescence is considered the result of complex interaction between external factors such as drought, high salinity and low temperatures (Marani et al 1985;Lim and Nam 2007) and internal factors such as plant hormones (Yong et al 2000;Dong et al 2008). Cytokinin and ABA are commonly identified phytohormones during research on leaf senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Given that senescence is a catabolic process that leads to nutrient recycling, chloroplast degeneration is one of the earliest events in the process. It is accompanied by a decrease in photosynthetic activity, chlorophyll degradation, and protein loss [39].…”
Section: Discussionmentioning
confidence: 99%